IL-10 is essential for the generation of germinal center B cell responses and anti-Plasmodium humoral immunity - Guthmiller, Jenna J. (J Immunol, 2016)
IL-10 is a pleiotropic cytokine expressed during malaria, a disease characterized by short-lived, parasite-specific antibody responses. The role of IL-10 in regulating B cell responses during malaria is not known. Here we report that IL-10 is essential for anti-Plasmodium humoral immunity. We identify that germinal center (GC) B cell reactions, isotype-switched antibody responses, parasite control, and host survival require B cell-intrinsic IL-10 signaling. IL-10 also indirectly supports humoral immunity by suppressing excessive IFN-γ, which induces T-bet expression in B cells. Genetic ablation of either IFN-γ signaling or T-bet expression in B cells substantially enhanced GC B cell responses and anti-Plasmodium antibody production. Together, our data show that B cell-intrinsic IL-10 enhances while B cell-intrinsic IFN-γ and T-bet suppress GC B cell responses and anti-Plasmodium humoral immunity. These data identify critical immunoregulatory circuits in B cells that may be targeted to promote long-lived humoral immunity and resistance to malaria.